Heat-related risk at Paris 2024: a proposal for classification and review of International Federations policies - Bandiera, D.; Racinais, S.; Garrandes, F.; Adami, P. E.; Bermon, S.; Pitsiladis, Y. P.; Tessitore, A. (British Journal of Sports Medicine, 2024)
Several International Federations (IFs) employ specific policies to protect athletes` health from the danger of heat. Most policies rely on the measurement of thermal indices such as the Wet Bulb Globe Temperature (WBGT) to estimate the risk of heat-related illness. This review summarises the policies implemented by the 32 IFs of the 45 sports included in the Paris 2024 Olympic Games. It provides details into the venue type, measured parameters, used thermal indices, measurement procedures, mitigation strategies and specifies whether the policy is a recommendation or a requirement. Additionally, a categorisation of sports` heat stress risk is proposed. Among the 15 sports identified as high, very high or extreme risk, one did not have a heat policy, three did not specify any parameter measurement, one relied on water temperature, two on air temperature and relative humidity, seven on WBGT (six measured on-site and one estimated) and one on the Heat Stress Index. However, indices currently used in sports have been developed for soldiers or workers and may not adequately reflect the thermal strain endured by athletes. Notably, they do not account for the athletes` high metabolic heat production and their level of acclimation. It is, therefore, worthwhile listing the relevance of the thermal indices used by IFs to quantify the risk of heat stress, and in the near future, develop an index adapted to the specific needs of athletes.